2020
DOI: 10.14814/phy2.14456
|View full text |Cite
|
Sign up to set email alerts
|

The secondary bile acids, ursodeoxycholic acid and lithocholic acid, protect against intestinal inflammation by inhibition of epithelial apoptosis

Abstract: Increased epithelial permeability is a key feature of IBD pathogenesis and it has been proposed that agents which promote barrier function may be of therapeutic benefit.We have previously reported the secondary bile acid, ursodeoxycholic acid (UDCA), to be protective in a mouse model of colonic inflammation and that its bacterial metabolism is required for its beneficial effects. The current study aimed to compare the effects of UDCA, LCA, and a non-metabolizable analog of UDCA, 6-methyl-UDCA (6-MUDCA), on col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 39 publications
4
49
0
3
Order By: Relevance
“…For instance, the impairments in intestinal permeability observed in C57/BL6 mice fed an HFD composed primarily of soybean oil (40% fat, absence of isoflavones, peptides) were found to significantly correlate with increases in cecal concentrations of primary bile acids, colic, chenodeoxycholic, and alpha-muricholic acid, as well as secondary bile acids lithocholic, hyodeoxycholic, and ursodeoxycholic acid, compared to control-fed mice [ 242 ]. While these findings are consistent with previous in vitro studies demonstrating that certain bile acids, including colic acid, chenodeoxycholic, and ursodeoxycholic acid, increase tight junction permeability [ 247 ], other studies, however, have reported a protective effect both in vivo and in vitro from ursodeoxycholic and lithocholic bile acid on intestinal inflammation [ 248 , 249 ]. In one study, the protective effect of fermented soy on permeability and concomitant reductions in lithocholic acid occurred in supplemented rats fed either a high- or low-fat diet composed primarily of beef tallow as the fat source [ 217 ], suggesting the soy-derived components such as peptides and isoflavones can mediate the pro-inflammatory HFD-induced shift in bile acids, although this requires further study.…”
Section: Mechanisms Of Actionsupporting
confidence: 91%
“…For instance, the impairments in intestinal permeability observed in C57/BL6 mice fed an HFD composed primarily of soybean oil (40% fat, absence of isoflavones, peptides) were found to significantly correlate with increases in cecal concentrations of primary bile acids, colic, chenodeoxycholic, and alpha-muricholic acid, as well as secondary bile acids lithocholic, hyodeoxycholic, and ursodeoxycholic acid, compared to control-fed mice [ 242 ]. While these findings are consistent with previous in vitro studies demonstrating that certain bile acids, including colic acid, chenodeoxycholic, and ursodeoxycholic acid, increase tight junction permeability [ 247 ], other studies, however, have reported a protective effect both in vivo and in vitro from ursodeoxycholic and lithocholic bile acid on intestinal inflammation [ 248 , 249 ]. In one study, the protective effect of fermented soy on permeability and concomitant reductions in lithocholic acid occurred in supplemented rats fed either a high- or low-fat diet composed primarily of beef tallow as the fat source [ 217 ], suggesting the soy-derived components such as peptides and isoflavones can mediate the pro-inflammatory HFD-induced shift in bile acids, although this requires further study.…”
Section: Mechanisms Of Actionsupporting
confidence: 91%
“…This revealed region-specific, barrier-stabilizing effects for the intestinal contents of RYGB-operated compared with sham-operated rats, possibly mediated by the action of various host- and/or microbiota-generated soluble factors. These potentially include, but are not limited to, hepatocyte-derived conjugated primary bile acids, that may become concentrated in the duodenum following RYGB due to redirection of ingested food passage to the mid-jejunum ( Ise et al., 2019 ), as well as microbiota-derived metabolites such as indole-3-propionic acid ( Jennis et al., 2018 ; Natividad et al., 2018 ), secondary bile acids ( Haange et al., 2020 ; Lajczak-McGinley et al., 2020 ), taurine ( Ahmadi et al., 2020 ; Wang et al., 2019a ), and the short chain fatty acid propionate ( Liou et al., 2013 ; Tong et al., 2016 ). Future metabolomics studies are required to confirm this, and to potentially discover novel soluble factors that stabilize the IEB.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary bile acid UDCA protects the intestinal barrier by inducing epithelial cell migration at the site of injury (86) and ameliorates LPS-induced intestinal inflammation (87). In addition, studies conducted on DSS-induced colitis mice model demonstrated the ability of UDCA and LCA to mitigate colonic inflammation by inhibition of epithelial apoptosis (88). Amino acids such as L-glutamine and L-arginine have been reported to regulate proliferation and differentiation of IECs suggesting the role for dietary supplements to regulate ER stress (89,90).…”
Section: Potential Therapeutics Targeting Er Stress In Ibdmentioning
confidence: 99%